GAMBARAN MEREK DAGANG DARI SEDIAAN SUNSCREEN YANG DIGUNAKAN SELURUH MAHASISWA PROGRAM STUDI DI UNIVERSITAS IMELDA MEDAN - Dini, Dea Aprian; Maya Syari, Dina; Siahaan, Mutiara (JIFI (Jurnal Ilmiah Farmasi Imelda), 2024)
Sun exposure can cause damage to the skin due to ultraviolet radiation. Skin needs special protection from ultraviolet rays, especially on skin organs, namely by using sunscreen. Sunscreen is a compound that functions to protect the skin from excessive exposure to ultraviolet rays. The type of research used is qualitative research using questionnaires to obtain student data. The population in this study was Imelda University Medan students at levels 1, 2, 3 and 4, totaling 1,333 people from 9 study programs. The data collection technique is using a questionnaire. The results of this research after data collection was carried out using a questionnaire and analyzed via SPSS, the results showed that there were 145 males at Imelda University in Medan who used sunscreen, while there were 715 females at Imelda University in Medan who used sunscreen, while sunscreen products the most popular one used by female students is Wardah 259 (19.4%). And the most popular product used by male students is Nivea Men 66 (4.9%). From this research it can be concluded that Wardah and Nivea Men products are the most popular at Imelda University Medan, and there are still many students who do not use sunscreen 473 (35.4%), consisting of male students 115 (8.6%) and 358 female students (26.8%), included in Imleda University, Medan. Even though sunscreen is really needed for the skin to protect it from ultraviolet rays.